Réponses

2014-04-04T15:24:54+02:00
Bonjour ,
A= 6/7 +15/7= 21/7= 3
B= 4/3-15/12= 4*4/4*3 - 15/12= 16/12 -15/12 = 1/12
C= 1/3-7/6 =2*1/2*3 -7/6 =2/6 -7/6 = - 5/6
D= 2/15 -(3/5 -4/3)= 2/15 - ( 3*3/5*3 -4*5/3*5) = 2/15-(9/15-20/15)=2/15 +11/15=13/15
E= 7/12-2/3 x 5/4=7/12-10/12= -3/12= -1/4
F= 3-2 x5/6= 3-10/6=3*6/6-10/6= 18/6-10/6= 8/6= 4/3
G= 9/4x 7/3 -5/6= 63/12-5/6=63/12 - 5*2/6*2=63/12 -10/12=53/12
H= 9/4x( 7/3 -5/6) = 9/4x( 7*2/3*2 - 5/6)= 9/4x(14/6-5/6)= 9/4x 9/6=81/24=27/8

Ps:
 x et * c'est multiplier